2000
DOI: 10.1016/s0002-9440(10)64630-5
|View full text |Cite
|
Sign up to set email alerts
|

BCL10 Expression in Normal and Neoplastic Lymphoid Tissue

Abstract: BCL10 is an apoptotic regulatory molecule identified through its direct involvement in t(1;14)(p22;q32) of mucosa-associated lymphoid tissue (MALT) lymphoma. We examined BCL10 protein expression in various normal tissues and B-cell lymphomas by immunohistochemistry of formalin-fixed and paraffin-embedded tissues using mouse BCL10 monoclonal antibodies. BCL10 protein was expressed in lymphoid tissue but not in 21 various other tissues with the exception of breast. In normal B-cell follicles, the protein was exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(172 citation statements)
references
References 26 publications
(27 reference statements)
8
155
0
9
Order By: Relevance
“…The tumor cells with t(1;14)(p22;q32) are characterized by strong uniformed BCL10 nuclear staining. 10 We previously showed that 5/5 cytogenetically proven t(1;14)(p22;q32) cases displayed strong BCL10 nuclear expression 9 (Du et al, unpublished data). In a recent study, we further confirmed t(1;14)(p22;q32) or its variants in 5/7 cases showing strong BCL10 nuclear expression by interphase FISH.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The tumor cells with t(1;14)(p22;q32) are characterized by strong uniformed BCL10 nuclear staining. 10 We previously showed that 5/5 cytogenetically proven t(1;14)(p22;q32) cases displayed strong BCL10 nuclear expression 9 (Du et al, unpublished data). In a recent study, we further confirmed t(1;14)(p22;q32) or its variants in 5/7 cases showing strong BCL10 nuclear expression by interphase FISH.…”
Section: Discussionmentioning
confidence: 95%
“…BCL10 immunohistochemistry was performed to attempt to identify evidence of t(1;14)(p22;q32) and both bone marrow and gastric biopsies showed strong homogeneous BCL10 nuclear expression in most if not all tumor cells (Figure 1a), similar to that seen in MALT lymphoma with t(1;14)(p22;q32) or its variants. 9,10 To verify whether the tumor cells harbor a BCL10 involved chromosomal translocation, interphase fluorescence in situ hybridization (FISH) was performed. 10 Although various pretreatments were tried, interphase FISH failed due to poor quality of the biopsy.…”
Section: Case Studymentioning
confidence: 99%
“…32 In contrast to normal lymphoid cells and to MALT lymphomas negative for the t(1;14)(p22;q32), MALT lymphomas harboring the t(1;14)(p22;q32) typically show high nuclear BCL10 expression. 33 By screening 331 MALT lymphomas immunohistochemically for BCL10 expression, Ye et al identified 12 cases (3.6%) comprising six gastric, five pulmonary, and one cutaneous MALT lymphoma, and confirmed the rearrangement of BCL10 by FISH in five of seven cases tested. 20 Our molecular cytogenetic study revealed BCL10 rearrangement in four of 252 cases (1.6%), two of which occurred in the colorectum and one each in the lung and salivary gland, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…78 The BCL10 protein is expressed predominantly in the cytoplasm of germinal center B cells, 79 whereas this protein is found to be strongly expressed in the nucleus of MALT lymphomas with t (1;14). 79 Moderate nuclear expression of BCL10 is also observed in nearly 100% of MALT lymphomas with the other translocation, t(11;18).…”
Section: Molecular Pathogenesis Of Malt Lymphoma M Nakagawa Et Almentioning
confidence: 99%